Development and reliability testing of an audit toolbox for the assessment of the physical activity friendliness of urban and rural environments in Germany - Müller, Christina; Domokos, Bruno; Amersbach, Tanja; Hausmayer, Eva-Maria; Roßmann, Christin; Wallmann-Sperlich, Birgit; Bucksch, Jens (Frontiers in Public Health, 2023)
1 Abstract Background According to socio-ecological theories, physical activity behaviors are linked to the physical and social neighborhood environment. Reliable and contextually adapted instruments are needed to assess environmental characteristics related to physical activity. This work aims to develop an audit toolbox adapted to the German context, to urban and rural settings, for different population groups, and different types of physical activity; and to evaluate its inter-rater reliability. Methods We conducted a systematic literature search to collect existing audit tools and to identify the latest evidence of environmental factors influencing physical activity in general, as well as in German populations. The results guided the construction of a category system for the toolbox. Items were assigned to the categories based on their relevance to physical activity and to the German context as well as their comprehensibility. We piloted the toolbox in different urban and rural areas (100 street segments, 15 parks, and 21 playgrounds) and calculated inter-rater reliability by Cohen’s Kappa. Results The audit toolbox comprises a basic streetscape audit with seven categories (land use and destinations, traffic safety, pedestrian infrastructure, cycling infrastructure, attractiveness, social environment, and subjective assessment), as well as supplementary tools for children and adolescents, seniors and people with impaired mobility, parks and public open spaces, playgrounds, and rural areas. 76 % of all included items had moderate, substantial, or almost perfect inter-rater reliability (κ>0.4). Conclusions The audit toolbox is an innovative and reliable instrument for the assessment of the physical activity friendliness of urban and rural environments in Germany.